Direct immunoassays and their performance – theoretical modelling of the effects of antibody orientation and associated kinetics. Issue 10 (6th September 2018) - Mackey, Dana; Kelly, Eilís; Nooney, Robert; O'Kennedy, Richard
Abstract : Mathematical and computational modelling are used to quantify immunoassay signals for various immobilized antibody orientations, antigen sizes and kinetic parameters, in order to determine optimal surface coverage. Abstract : The orientation and activity of antibodies immobilized on solid surfaces are of direct relevance to many immunosensing applications. We therefore investigate a mathematical model which estimates the fraction of antibodies which are available for reaction in a randomly adsorbed sample. Numerical simulations are presented which highlight the separate effects of antibody orientation, accessibility and loss of binding ability on the amount of captured antigen. The assay response can then be expressed as a function of total antibody density and used for optimizing the surface coverage strategy under various conditions.